A study on ICT related issues for school-based assessment online system in Malaysian secondary education - Abas, Azizi; Rasali, Rosham; Rahmat, Abdul Razak (WSEAS - World Scientific and Engineering Academy and Society, 2014)
School-based assessment is one of the initiatives under the Multimedia Super Corridor Malaysia that was introduced in the year 2010.The implementation of the SPBBS online system is an introduction of a new method of recording and reporting system for students’ activities and academic achievement. This online system has been reported to trigger issues from the teachers as the major stakeholders in the system development and deployment.The online SPBBS system is claimed to be difficult to access and slow in response.The objective of this study is to identify, whether the claimed made is true or on the contrary.In ICT aspect, what is the element that causes the main problem? The infrastructure such as internet connectivity and hardware and knowledge of the users are studied. Surveys and interviews with the relevant parties were conducted, namely the teachers from Sekolah Menengah Sultanah Asma, Alor Setar, Kedah as well as the officers from Bahagian Teknologi Pendidikan Negeri Kedah. Comparison of data and information gathered are analyzed. Facts and findings should show that the problem would generally circulate around the internet capacity, hardware involved and ICT knowledge of the respondents or parties involved. The tasks and perception of each user involved are also evaluated.